Doping Indium Oxide Films with Amino‐Polymers of Varying Nitrogen Content Markedly Affects Charge Transport and Mechanical Flexibility. (12th June 2021) - Wang, Zhi; Zhuang, Xinming; Wang, Binghao; Huang, Wei; Marks, Tobin J.; Facchetti, Antonio
Abstract: Here, correlations between polymer structure and charge transport in solution‐processed indium oxide, In2 O3 :polymer blend flexible thin film transistors (TFTs) are investigated using four polymers having electron‐donating amine functionalities (polyethyleneimine (PEI), poly(allylamine), polyethyleneimine ethoxylated (PEIE), and PVP‐NH2 (PVP; poly(4‐vinylphenol)), and two PEI‐PEIE mixtures) with varied atomic amine nitrogen content (N%) of 12.6, 9.1, 6.9, 2.6, respectively. These amino‐polymers influence the semiconducting oxide film TFT electron mobilities via a delicate interplay of electron transfer/doping, charge generation/trap‐filling, film morphological/microstructural variations, which depend on the polymer structure, thermal stability, and N%, as well as the polymer content of the In2 O3 precursor and the carbon residue content in In2 O3 . Thus, increasing the N% from 0.0% in the control PVP to 12.6% in PEI increases the electron doping capacity, the polymer content of the blend formulation, and the blend TFT field‐effect mobility. Optimal polymer incorporation invariably enhances charge transport by as much as ≈2×, leading to a maximum carrier mobility of 8.47 ± 0.73 cm 2 V −1 s −1 on rigid Si/SiO x substrates and a remarkable 31.24 ± 0.41 cm 2 V −1 s −1 on mechanically flexible polyimide/Au/F:AlO x substrates with Al contacts. Furthermore, all of the polymers equally enhance the mechanical durability of the corresponding In2 O3 :polymer blend TFTs with respect to mechanical stress. Abstract : The correlations between polymer structure, electron‐donor nitrogen content, polymer thermal decomposition properties, and carbon contamination of the metal oxide matrix as well as degree of crystallinity in flexible indium oxide (In2 O3 ):polymer blend thin film transistors are investigated, demonstrating the role of all of those parameters in affecting charge transport.